Tri-Spine Horseshoe Crab Aquaculture, Ranching and Stock Enhancement: Perspectives and Challenges - Xu, Peng; Bai, Haiwei; Xie, Xiaoyong; Wang, Chun-Chieh; Huang, Xing; Wang, Xueping; Zhang, Mingming; Ye, Zhenyu; Zhu, Junhua; Zhen, Wenquan; Cheung, Siu Gin; Shin, Paul K. S.; et al. (Frontiers in Marine Science, 2021)
As a well-known example of “living fossil,” horseshoe crabs are ecologically significant macroinvertebrates in coastal and estuarine ecosystems. The tri-spine horseshoe crab, Tachypleus tridentatus, has been widely utilized for Tachypleus amebocyte lysate production and food consumption since the 1980s, which led to considerable population declines along the west coast of the Pacific Ocean. The declining horseshoe crab population is expected to have ecological and social impacts. Stock enhancement through captive rearing of juveniles is cited as an important alternative to repopulate the native T. tridentatus, which in turn supports sustainable resource utilization and research activities. The hatchery production techniques for this species have gradually developed following the mass culture efforts in Japan since the late 1980s. However, the previous studies have primarily concerned the feed types and husbandry conditions to maximize the growth and survival of the juveniles. Little is known about the practicability and effectiveness of releasing large numbers of hatchery-bred individuals through releasing programs. In this review, we (1) summarize the available captive breeding and rearing techniques, (2) discuss the release strategies that could potentially improve the survival of released juveniles, and (3) identify the future opportunities and challenges in establishing technical frameworks to support responsible stock enhancement programs for T. tridentatus. The information should benefit future horseshoe crab fisheries management efforts in the attempt to restore the severely depleted populations.